Analisis Motivasi Belajar House Keeping Praktek Terhadap Prestasi Belajar Mahasiswa Sekolah Tinggi Pariwisata Trisakti - Darsiah, Anis (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
This study purpose to find how big relationship between motivation to study house keeping part II practices toward student’s learning achievement at the fourth semester of Tourism Institute in Trisakti. It can improve knowledge and finding that individual study motivation will become the result of studying achievement has increased, while Tourism Institute in Trisakti especially for coordinator and lecturer of housekeeping discipline. This report can be used as input or consideration support on improving student’s motivation to study housekeeping part II and finding the way which can be applied to enhance or improve student’s studying achievement. Research method used a descriptive method and correlation to find how big relationship between studying motivation toward studying achievement. Collecting primary data used observation method where the questionnaires were distributed to students, while the secondary data were obtained from the various library materials. This study concluded that studying motivation will effect to studying achievement and having relationship of medium correlation that was 0.52. Studying motivation effected 27.04% of student’s studying achievement, especially for discipline of housekeeping part II practices at Tourism Institute in Trisakti, while the remains of 72.96% were effected by another factors which were not examined at the end of this project